2022
DOI: 10.1038/s41419-022-05496-z
|View full text |Cite
|
Sign up to set email alerts
|

Matrix protein Tenascin-C promotes kidney fibrosis via STAT3 activation in response to tubular injury

Abstract: Accumulating evidence indicates that the extracellular matrix (ECM) is not only a consequence of fibrosis, but also contributes to the progression of fibrosis, by creating a profibrotic microenvironment. Tenascin-C (TNC) is an ECM glycoprotein that contains multiple functional domains. We showed that following kidney injury, TNC was markedly induced in fibrotic areas in the kidney from both mouse models and humans with kidney diseases. Genetically deletion of TNC in mice significantly attenuated unilateral ure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…TNC is the rst member of the tenascin family to be discovered, which mainly mediates cell adhesion and extracellular matrix 17 . As reported, TNC can modulate cell cycle of neural stem cells 18 , promote brosis in tubular injury of kidney 19 , and take part in ovarian cancer migration 20 . But the role of TNC + broblasts in human skin diseases is completely unknown.…”
Section: Introductionmentioning
confidence: 76%
“…TNC is the rst member of the tenascin family to be discovered, which mainly mediates cell adhesion and extracellular matrix 17 . As reported, TNC can modulate cell cycle of neural stem cells 18 , promote brosis in tubular injury of kidney 19 , and take part in ovarian cancer migration 20 . But the role of TNC + broblasts in human skin diseases is completely unknown.…”
Section: Introductionmentioning
confidence: 76%
“…At the same time, more and more studies have confirmed the functions of THBS2 in diverse fibrosis, even in PF [41][42][43][44]. FAP and TNC genes as biomarkers have been proved in liver fibrosis and kidney fibrosis [45,46]. The relative RNA expression and protein levels of ADAMTS16 elevated in mice with cardiac fibrosis [47].…”
Section: Discussionmentioning
confidence: 98%
“…Ретинол-связывающий белок и кининоген-1 являются маркерами повреждения клеток тубулярного эпителия и, по данным других авторов, факторами, ассоциированными с отсутствием ответа на стероиды [21,22]. Об интенсивности накопления ЭЦМ свидетельствует выделение с мочой больных с ФСГС люмикана, тенасцина X и нейрофилина-2 [23][24][25].…”
Section: Discussionunclassified